Implementasi Akad Wakalah pada Fintech Peer-To-Peer (P2P) Lending di Indonesia (TAWAZUN: Journal of Sharia Economic Law, 2022)
This study aims to analyze the implementation of wakalah contracts in fintech peer to peer lending in Indonesia. This study uses a qualitative approach with data collection techniques using literature study. The results of this study found that Alami and Investree companies provide financing products based on factoring with Wakalah bil Ujrah contracts that are in accordance with sharia provisions. Meanwhile, the financing products from Dana Syariah Indonesia are not fully in accordance with sharia provisions because there are still misconceptions in practice.